Liderazgo transformacional y la eficacia de la gestión pedagógica de directivos en la IEPSPM N° 6010227 Club de Leones Lemgo Alemania San Juan Loreto 2014 - Perez Flores de Salazar, Maria Teodora (2022)
In the present study carried out in the Peruvian Amazon, the general objective was to determine the relationship between transformational leadership and the effectiveness of the pedagogical management of Directors in the IEPSPM N ° 6010227 Lemgo Germany Lions Club of the district of San Juan, in Loreto, in 2014. The type of research was descriptive, with a bivariate, cross-sectional, and field design. The population and the sample of the investigation were 46 between directors and teachers of the educational institution. The survey technique was applied with two questionnaires for data collection, before this process it was necessary to validate them through expert judgment, in addition to determining their reliability. The results show that Spearman's rho correlation coefficient = 0.378**, p = 0.010 indicates a low significant direct relationship between transformational leadership and the effectiveness of the pedagogical management of managers in the IEPSPM N° 6010227 Lemgo Lions Club Germany, San Juan, Loreto, which also demonstrates the hypothesis proposed for the investigation.